Motivational Dimensions in Language Learning: A Case Study of Vocational College Students Choosing Japanese Language Stream - Patria, Aditya Nur; Alfarisy, Fitri (Vocational College of Diponegoro University, 2024)
Motivation is still taken into consideration when ones apply to a minor in a study program with limited seats. The present study explores students’ motivational dimensions for choosing Japanese language stream which has limited quota in an Indonesian vocational college. Based on responses from 43 first-year students choosing Japanese stream, it was found that ‘personal goals’ dominated the list of motivational dimensions. In contrast, no student expressed ‘external pressures/incentives’ as their motivation. Following screening process conducted by the study program, ‘personal goals’ maintained its position as the most frequently expressed motivation. Moreover, ‘academic interests’ appeared as the motivational dimension which did not change in number following screening process. These results demonstrate the attraction of the internship program in Japan promoted by the study program in recent years.